THE BAT SPECIES IN CAMOTES ISLANDS, CEBU, PHILIPPINES - Malaki, AB; Agbay, EA; Alcazar, SMT; Lillo, EP; Alburo, HM; Opiniano, RP; Obiso, LS; Hoyohoy, GB; Manalastas, RDC; Rica, RLV (Journal of Agriculture and Technology Management, 2008)
The study was conducted to assess the bat species in Camotes group of Islands, Cebu, Philippines. It specifically aimed to identify species composition and relative abundance of bats in the study sites. The assessment was undertaken from 16-20 May 2005 in the two sampling sites, Montealegre, San Francisco and Pagsa, Poro respectively. Thirty five mm mesh monofilament mist nets 4m x 6m in dimension were used to capture the bats and mounted at different elevational gradient (upper slope, middle slope and lower slope), along flyways, across ridges, ravines and near fruting trees. Ingle and Heaney's Key to the Bat of the Philippine Island (1992) was used in the bat identification. A total of 101 bats representing the different speciesof fruit bats (Megachiroptera:Pteropodidae) were netted. Seventy nine individuals were captured in Pagsa and Twenty two in Montealegre respectively. Of which fifty species of the common Short-nosed Fruit Bat ( Cynopteros bracyotis ), 32 were the Common Rousette ( Rousettus amplixicaudatus ) and 14 were the Dagger-toothed Flower Bat ( Macroglossus minimus). Results also showed that the abundant fruit bat species in the area was the Cynopteros bracyotis followed by the Rousettus .  amplexicaudatus  and the lowest was Macroglossus. minimus.  There were no insect bats captured, this could be attributed to the fact that insect bats have the ability to echolocate and enable to evade the nets (Sedlock, 2001). The presence of these bats indicate that the forest habitat in Camotes group of islands is already disturbed and degraded therefore, conservation efforts of the island is imperative. Information, education and communication must be fully intensified to upgrade the awareness and attention of the populace with regard to the importance of biodiversity conservation and protection particularly on bats.